Propuesta de implementación de las Buenas Prácticas de Manufactura (BPM) para la planta embotelladora de agua Akascia ubicado en la provincia de Imbabura. - Gómez Erazo, Alan Israel (2025)
This research focuses on the Proposal for Implementing Good Manufacturing Practices (BPM) for the “Akascia” water bottling plant in the Imbabura Province. The objective was to develop a proposed Good Manufacturing Practices (BPM) manual for the water bottling plant. The research was quantitative, obtaining percentages by applying the Checklist, and qualitative, assessing compliance with hygiene standards. It has a non-experimental, cross-sectional design. The data collection techniques used were the Checklist, which identified the company's initial condition, the Pareto chart for the subsequent situational diagnostic analysis, and the Cause-Effect Analysis, which identified factors influencing noncompliance with the items. The population and sample consisted of the water bottling plant. The results of the situational diagnosis revealed a 57.14% level of noncompliance with BPM at the water plant, highlighting several nonconformities that required immediate attention. Upon analyzing the data, it was found that eleven aspects were below 80%. The emphasis was on hygiene requirements, raw materials and inputs, production operations, storage, packaging, labeling, and transportation. The conclusion is that the BPM manual is a fundamental tool for ensuring product safety, maintaining quality standards, and safeguarding consumer health.